Wage Growth and Inflation in Europe : A Puzzle? - Boranova, Vizhdan (IMF Working Papers; Working Paper ;, 2019)
Wages have been rising faster than productivity in many European countries for the past few years, yet signs of underlying consumer price pressures remain limited. To shed light on this puzzle, this paper examines the historical link between wage growth and inflation in Europe and factors that influence the strength of the passthrough from labor costs to prices. Historically, wage growth has led to higher inflation, but the impact has weakened since 2009. Empirical analysis suggests that the passthrough from wage growth to inflation is significantly lower in periods of subdued inflation and inflation expectations, greater competitive pressures, and robust corporate profitability. Thus the recent pickup in wage growth is likely to have a more muted impact on inflation than in the past.